Projected changes of Greenland’s periphery glaciers and ice caps - Limin Kang; Minghu Ding; Yuzhe Wang; Weijun Sun; Lei Wang; Hongmin An; Qinglin Zhang; Jiahang Che; Baojuan Huai (Environmental Research Letters, 2024)
Rapid global warming has caused drastic mass loss in Greenland’s peripheral glaciers and ice caps (GICs), contributing to a rise of global sea levels. To better understand future changes under different emission scenarios, we used the Open Global Glacier Model to simulate glacier dynamics and runoff changes from 2015 to 2100. The results show that their area and volume will decrease by 38.88% (SSP1-2.6) to 60.84% (SSP5-8.5) and 47.56% (SSP1-2.6) to 67.10% (SSP5-8.5) by 2100, with regions that have larger glacierized areas and are farther from the ocean experiencing less volume loss. Meanwhile, the predicted surface mass balance of Greenland’s peripheral GICs in 2100 is −0.58 ± 0.92, −1.18 ± 1.13, −2.04 ± 0.79 and −3.16 ± 0.96 m w.e. a ^−1 under four emission scenarios. The runoff under higher emission scenarios is larger than that under lower emission scenarios, with peak water occurring later in regions that have larger glacierized areas and are farther from the ocean.